PENGARUH IKHTILAF AL-MATHALI’ TERHADAP PENENTUAN AWAL BULAN DALAM PERSPEKTIF MAZAHIB AL-ARBA’AH - Rahwan; Moh. Hafid (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Almost every time before Ramadan, Shawwal and Dhulhijjah Muslims are always busy with the issue of determining the beginning of the month, Indonesia is no exception. Has the new moon been seen or not?, will tomorrow turn into a month or not? and so forth. So we often encounter it in an area, different from other regions in determining the beginning and end of the month (hijri).There are two ways for Muslims to determine the beginning and end of Ramadan, namely: rukyat and reckoning. Rukyat is a method of determining the beginning of the month by watching the new moon rise into the sky at sunset towards the beginning of the month. While reckoning is a method to determine the beginning of the month by perfecting the previous month (to 30 days) when seeing the new moon is no longer possible.In the rukyatul hilal, it seems that the hilal cannot cover the entire existing hemisphere. This means that at the first sighting of the new moon, some parts of the earth can see the new moon and some cannot. This of course raises problems for regions that cannot see the hilal for the first time, is it also related to legal provisions and consequences (from regions that have seen the hilal appear)? or each region has its own provisions and laws without following other regions? In this study, the author will describe the problem (mazahib al-arba'ah perspective) by researching the type of library (library research) through data from books, books, journals, articles and so on.Scholars have different opinions regarding the application of matlak to other regions that do not witness the issuance of the new moon: a). According to the majority of scholars (Hanafi, Maliki & Hambali), the area that has seen the new moon can cover all existing places, so that the entire area also experiences a change at the beginning of the month. b). According to (the majority) Syafi'iyah, for areas that have seen the new moon experience the beginning of the month, while other areas (as far as four farsakh and above) have not, so that the area managed to see the new moon separately.